2011
DOI: 10.1523/jneurosci.1163-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Default Mode Network Connectivity Predicts Sustained Attention Deficits after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) frequently produces impairments of attention in humans.These can result in a failure to maintain consistent goal-directed behavior. A predominantly right-lateralized frontoparietal network is often engaged during attentionally demanding tasks. However, lapses of attention have also been associated with increases in activation within the default mode network (DMN). Here, we study TBI patients with sustained attention impairment, defined on the basis of the consistency of their behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
335
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(378 citation statements)
references
References 71 publications
38
335
1
4
Order By: Relevance
“…We have previously shown that after TBI, FA measurements in particular WM tracts relate to multiple neuropsychological domains 10, 11, 46. In a separate cross‐sectional cohort of patients after moderate–severe TBI and controls who were scanned once, we confirmed both lower SPCC FA and lower immediate verbal memory recall in patients after TBI compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…We have previously shown that after TBI, FA measurements in particular WM tracts relate to multiple neuropsychological domains 10, 11, 46. In a separate cross‐sectional cohort of patients after moderate–severe TBI and controls who were scanned once, we confirmed both lower SPCC FA and lower immediate verbal memory recall in patients after TBI compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…Further, the increased connectivity within the DMN that we observed has been interpreted by some as a compensatory response to trauma. 14,15 For example, Sharp and colleagues found that faster performance on an attentional task was associated with greater within-DMN connectivity at rest. 15 These investigators also found that increased precuneus-DMN functional connectivity at the beginning of a task resulted in less-variable reaction times during the task, and concluded that this elevated functional connectivity supports performance.…”
Section: Venkatesan Et Almentioning
confidence: 99%
“…Studies of TBI have reported increased within-DMN functional connectivity during task performance, featuring prominently the PCC and precuneus regions. 14,15 In addition, graph theoretical approaches have found support for a breakdown of the PCC as a central DMN ''hub'' after injury, resulting in a more disorganized connectivity profile, when compared to healthy individuals. functionally connected to a number of distinct and distributed brain systems, [17][18][19] and this region shows alterations in functional connectivity in a number of patient samples, compared to matched controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structural corticothalamic abnormalities of white matter in TBI patients are linked to more serious symptoms including posttraumatic stress disorder (Yeh et al., 2014). Obtained results cannot directly explain decreased connectivity linked to the DMN reported by previous studies (Bonnelle et al., 2011; Sharp, Scott, & Leech, 2014; Sharp et al., 2011). Our analysis is in favor of a stronger anticorrelation relationship between DMN and other cortical regions.…”
Section: Discussionmentioning
confidence: 99%